Underrecognition and undertreatment for peripheral arterial disease in diabetic patients in Thailand - Supapong Arworn (2018)
© 2017, Medical Association of Thailand. All rights reserved. Objective: Although several guidelines emphasized the importance of atherosclerotic risk factor management in peripheral arterial disease (PAD) in diabetic patients to reduce the cardiovascular mortality, authors do not know to what extent physicians follow these guidelines. Material and Method: Between May 2014 and August 2014, consecutive eligible outpatients, aged ≥45 years with established DM, were invited to be involved in this study. History, physical exam and laboratory test were reviewed. Ankle brachial index ≤0.9 was considered PAD. Then patients were evaluated the percentage of risk factor control according to American Heart Association (AHA) criteria. The good control was defined that patients have adequate risk factor control between 3-5 factors. Results: 2,247 diabetic patients were recruited for the study. 286 patients out of 2,247 were diagnosed PAD (12.7%). 236 PAD patients (82.5%) did not have any symptom of intermittent claudication, rest pain, gangrene or ulcer. According to AHA criteria, the percentage of adequate control in low density lipoprotein, HbA1C and systolic blood pressure in PAD patients was 18.9, 30.1 and 33.2% respectively. 49.8% in PAD patients had met our good risk factor control criteria. Conclusion: Most PAD in diabetic patients was asymptomatic. The atherosclerotic risk factor control was poor in this group.